Overexpression of the PeaT1 Elicitor Gene from Alternaria tenuissima Improves Drought Tolerance in Rice Plants via Interaction with a Myo-Inositol Oxygenase - Shi, Fachao; Dong, Yijie; Zhang, Yi; Yang, Xiufeng; Qiu, Dewen (Frontiers in Plant Science, 2017)
Abiotic stresses, especially drought, seriously threaten cereal crops yields and quality. In this study, we observed that the rice plants of overexpression the Alternariatenuissima PeaT1 gene showed enhanced drought stress tolerance and increased the survival rate following a drought treatment. In PeaT1-overexpressing (PeaT1OE) plants, abscisic acid (ABA) and chlorophyll content significantly increased, while the malondialdehyde (MDA) content decreased compared with the wild-type plants. Additionally, we confirmed that the transcript levels of drought-responsive genes, including OsAM1, OsLP2, and OsDST, were prominently lower in the PeaT1OE plants. In contrast, expression levels of genes encoding positive drought stress regulators including OsSKIPa, OsCPK9, OsNAC9, OSEREBP1, and OsTPKb were upregulated in PeaT1OE plants. Furthermore, combing the yeast two-hybrid assay, we found that PeaT1 could interact with amyo-inositol oxygenase (OsMIOX), which was verified by pull-down assay. Interestingly, OsMIOX was highly expressed in PeaT1OE plants during the drought treatment. Additionally, the OsMIOX-GFP fusion protein co-localized with the endoplasmic reticulum (ER) marker in tobacco protoplasts, suggesting OsMIOX performs its function in ER. Therefore, our results are useful for elucidating the molecular mechanism underlying the improvement of drought tolerance by PeaT1.